An opportunity lost the Truman administration and the farm policy debate - Dean, Virgil W.; ebrary, Inc. (Columbia : University of Missouri Press, 2006)
"Examines Charles Brannan's agricultural plan, the farm policy debate, and Harry S. Truman's quest for a long-range agricultural program. Assesses Truman's relationships with farmers and with politicians and the search for a workable peacetime program, especially as it related to the parity price foundation and price supports"--Provided by publisher.
Introduction -- The search begins -- The Eightieth Congress tries to "fix the roof" -- Farm policy and the election of 1948 -- The Brannan farm plan: agricultural panacea or political football? -- Reaction to the Brannan plan -- The Brannan plan in Congress -- The Brannan plan in 1950.
Includes bibliographical references (p. 243-261) and index.
Electronic reproduction.
Keywords: Agriculture and state -- United States -- History -- 20th century; Electronic books